Processamento e caracterização térmica da laterita para aplicação na construção civil - Rafaela Marques Silva (2024)
The civil construction sector conducts research to make its activities more sustainable and economical. Research is being conducted to develop and employ new materials and processes that meet environmental and socioeconomic sustainability criteria without reducing the reliability and durability of existing materials and processes. In this context, there is laterite, a type of soil abundant in various geographic regions and widely used in the history of civil construction. The objective of this work was to process and characterize a new laterite-based ceramic tile and to obtain a standard for test specimens with properties that can be used as a low-cost material, designing and producing a new construction product within ABNT standards that meets market demands. The processing of the samples was carried out by crushing the laterite clods to a granulometry of 45 Mesh. The samples in the form of pellets were obtained by pressing the laterite powder with a load of 1.5 ton/cm². The pellets were subjected to different sintering processes, using a 100 °C interval, starting from room temperature up to 600 °C. These samples were subjected to TG and DSC thermal analyses, MEV, EDS, DRX, FTIR, and Vickers microhardness tests. The test specimens in the form of ceramic plates were obtained by pressing the laterite powder using an isostatic press at a gauge pressure of 140 Kg/cm². The test specimens were sintered in the same way as the pellets and subjected to dimensional analysis, water absorption test, and three-point bending test. The results of the TG and DSC analyses showed thermal stability after 600 °C and two endothermic peaks, the first related to the transition of the gibbsite and nacrite phases to form the kaolinite phase, and the second endothermic peak is associated with the dehydroxylation of kaolinite. The MEV results showed through micrographs an excellent degree of homogeneity of the samples and a decrease in porosity as a function of sintering temperature. With EDS, it was possible to identify the presence of Fe and Al oxides in higher concentration in the samples. The DRX results showed the transition of the gibbsite and nacrite phases to form the kaolinite phase and the transition of kaolinite, which after undergoing dehydroxylation, transformed into amorphous metakaolinite. FTIR showed the stability of the functional groups of the minerals identified in the material at sintering temperatures of 300 °C and 600 °C. The Vickers microhardness test showed the influence of sintering temperature on the increase in sample hardness. Dimensional analysis showed the morphological and geometric homogeneity of the ceramic plates. The water absorption test showed indices according to the standards for ceramic plates sintered from 300 °C to 600 °C. The three-point bending test showed that the ceramic plate sintered at 600 °C had the highest flexural strength modulus. It was concluded that the laterite ceramic plates sintered between 300 °C and 600 °C meet current water absorption standards, being classified as ceramic plates belonging to Group III, with high water absorption and dry pressed. According to the results obtained, the laterite ceramic plates sintered between 300 °C and 600 °C can be applied in civil construction, and the sintering of these ceramic plates is fundamental for increasing the hardness and flexural strength modulus. Keywords: Ceramic, Sustainability, Sintering, Soils, Weathering.